World Vaping Day: Contextualizing Vaping Culture in Online Social Media Using a Mixed Methods Approach. (April 2019) - Colditz, Jason B.; Welling, Joel; Smith, Noah A.; James, A. Everette; Primack, Brian A.
Few studies have demonstrated the use of mixed methods research to contextualize health topics using primary data from social media. To address this gap in the methodological literature, we present research about electronic nicotine delivery systems, using Twitter data from "World Vaping Day." To engage with the quantitative breadth and qualitative depth of 5, 149 collected tweets, we utilized a convergent parallel mixed methods framework, integrating thematic prevalence estimates with phenomenological contextualization. Sentiment was more positive than negative across all categories except policy related. A total of 23% of tweets were promotional and relatively few tweets related to tobacco use (4.9%) or health concerns (4.2%). Salient themes included modifying or upgrading electronic nicotine delivery systems devices, and general mistrust of public health advocates and tobacco companies.